Association between walking speed and calcaneus stiffness index in older adults - Zhou, Tang; Wang, Jingjing; Li, Yiyan; Lu, Yanhua; Liu, Jiajia; Hong, Jintao; Quan, Minghui; Wang, Dao; Chen, Peijie (Journal of bone and mineral metabolism, 2023)
Introduction The aim here is to examine the association between objectively measured usual walking speed (UWS) and bone status in community-dwelling older Chinese. Materials and methods This is a cross-sectional study of a population of 1528 adults (817 females, mean age 68.5 ± 5.3; 711 males, mean age 69.1 ± 5.2) aged 60–79, living in communities in Shanghai. Walking speed was assessed using a 4-m walk test at a usual-pace walking speed a walking speed at which the subject felt relaxed—and bone status measured by quantitative ultrasound (QUS). The health-related characteristics of participants include family background, physical activity level, chronic disease, smoking and alcohol consumption, frequency of falls, vitamin intake, and hormone therapy. Results Multiple linear regression is used to analyses any association between UWS and bone status, adjusting for confounding factors showing a significant association between faster UWS and a higher calcaneal stiffness index (SI) (p < 0.01). Comparing the lowest quartile of the data set with the highest at UWS, a high SI is achieved with 5.34 (95% CI = 3.22, 7.46) (p < 0.01), after adjusting for confounders. An increase of 1 dm/s was associated with a 0.91 (95% CI = 0.53, 1.29) increase in SI. This relationship for most subgroups is consistent. Conclusion Our findings suggest that UWS can be a sensitive indicator of calcaneal bone loss among an older population.